Analisis Penentuan Karyawan Tetap Dengan Algoritma K-Means Dan Davies Bouldin Index - Bobby Kristanto; Ahmad Turmudi Zy; M. Fatchan (Bulletin of Information Technology (BIT), 2023)
Developments Technological advances are things that cannot be avoided in this life because technological developments go hand in hand with advances in science. With the rapid development of technology today, of course it affects the work environment as well. Employees are one of the company's reasons for determining the continuity of business activities. Employee work contracts within the company are important and must be considered in order to achieve company goals. PT. Taewon Indonesia is engaged in paper production and has more than 300 contract workers, making it difficult to select or expel workers who are still suitable and meet the requirements of the contract extension process. Analysis of determining permanent employees is very important for companies to determine recruitment strategies and human resource development. This study analyzes the determination of permanent workers using two clustering algorithms, K-Means and Davies Bouldin Index. K-Means is used to collect employee data based on certain criteria, while the Davies Bouldin Index is used to measure the quality of clustering results. Of the 455 employee performance appraisal datasets, tests were carried out by determining 2 clusters and validation was tested with the Davies Bouldin Index. And the resulting -1.752. Based on the results obtained, it shows that the k-means algorithm can be implemented in clusters to determine permanent workers with fairly good validation results